1981
DOI: 10.1159/000123224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraventricular β-Endorphin and Morphine on Hypothalamic-Pituitary-Adrenal Activity and the Release of Pituitary β-Endorphin

Abstract: The effects of intraventricular (i.v.t.) morphine sulfate (MS) and β-endorphin (β-EP) on pituitary-adrenal activity and the release of pituitary β-EP were studied in rats. Pituitary-adrenal activity was monitored by measuring plasma corticosterone (CS) levels. 45 min after i.v.t. injection, both MS and β-EP caused dose-related increases in plasma CS, with β-EP being approximately ten times more potent on a molar basis. MS injected i.v.t. at 0.3, 1.0, 3.0 and 10.0 μg did not cause a significant reduction in pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Opiates are believed to play an important role in the control of the HPA. In rats, acute administration of both morphine and its antagonist, naloxone results in HPA axis activation [18, 19], while repeated morphine treatment can cause chronic stress symptoms [20,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Opiates are believed to play an important role in the control of the HPA. In rats, acute administration of both morphine and its antagonist, naloxone results in HPA axis activation [18, 19], while repeated morphine treatment can cause chronic stress symptoms [20,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Several effects of opioid peptides and opioid drugs on the neuro-endocrine system have been rather well established [for reviews, see 18, 30], Thus, in addition to the regulatory effects of DA and NA mentioned above, also opioids have been reported to affect the secretion of LH [31,38,53,58] and prolactin [25,58]. Moreover, the hypo thalamus-pituitary-adrenocortical axis, involved in stress re sponses, appears to be stimulated by morphine [2,3,13] as well as other opioid agonists [9,19]. However, little is known about the possible mechanisms (either direct or via modulation of monoamine release) by which opioids exert their effects on hor monal processes.…”
mentioning
confidence: 99%
“…Some reports have demonstrated that morphine-induced increase in SCS levels is also mediated by the central nervous system. For example, increase in plasma corticosterone levels was produced by intraventricular (25) or intrahypothalamic injection (26) of morphine, and the effect of morphine on the hypothalamicpituitary-adrenal (HPA) axis was absent in hypothalamic lesioned (27) and hypophysectomized (28) rats. In vitro studies also demonstrated that morphine stimulated secretion of corticotropin-releasing factor (CRF) in the isolated hypothalamus but not of adrenocorticotropic hormone (ACTH) in the pituitary segments (29).…”
Section: Discussionmentioning
confidence: 99%